How do you find the answer of -22-x=5+6x+9???

Answers

Answer 1
Answer: -22-x=5+6x+9
-6x-x=22+5+9
-7x=36
x=5.142

Related Questions

please help me on this I'm struggling on this thanks for your helping of you answer.please show your work:-)
Suppose that a diamond weighs 0.0182 carat.What is that number in expanded form
3+z=-19 true, false, or open
Please help!!!!!#34
25% of the money is £35 what is the whole amount?

Estimate the product of 496 and 351

Answers

Take 496 and round it to 500
Take 351 and round it to 350 
Your answer should be around 850

Mrs t class is taking a field trip to the zoo the trip will cost $26for each student there are 22 student in class

Answers

572 is the answer, I think.
22x26. Is 572 it will cost

The smallest and the largest whole numbers that round to 70 when rounded to the nearest ten. What are the numbers....

Answers

The smallest is 65. The largest is 74.
Smallest ⇒ 65

Largest 
74

Jesse is putting a ribbon around a square frame he uses 24 inches of ribbon how long is each side of the frame

Answers

Each side of the frame is 6 inches long
Each is 6 inches long✌️

Pls help :) solve. b-^4 =1/81 b

Answers

b^(-4) =(1)/(81)\n\nb^(-4) =(1)/(b^4)\n\n(1)/(b^4)=(1)/(81)\n\nb^4 = 81\n\nb^4 = 3^4\n\nb^4 = (-3)^4\n\n\boxed{\bf{b = 3}}\n\n\boxed{\bf{b=-3}}

What are the solutions to the system of equations?

Answers

Answer:

A. (1,5) and (5,13)

Step-by-step explanation:

We have been given a system of equations. We are asked to find the solution of our given system.

\left \{ {{y=x^2-4x+8}\atop {y=2x+3}} \right.

Equate both equations:

x^2-4x+8=2x+3

x^2-4x-2x+8-3=2x-2x+3-3

x^2-6x+5=0

Split the middle term:

x^2-5x-x+5=0

x(x-5)-1(x-5)=0

(x-5)(x-1)=0

Use zero product property:

(x-5)=0\text{ (or) }(x-1)=0

x=5\text{ (or) }x=1

Now, we will substitute both values of x, in our given equation to solve for y.

y=2x+3

y=2(1)+3

y=2+3

y=5

One solution: (1,5)

y=2x+3

y=2(5)+3

y=10+3

y=13

2nd solution: (5,13)

Therefore, option A is the correct choice.

Answer:

A

Step-by-step explanation:

Given the 2 equations

y = x² - 4x + 8 → (1)

y = 2x + 3 → (2)

Since both express y in terms of x we can equate the left sides, that is

x² - 4x + 8 = 2x + 3 ( subtract 2x + 3 from both sides )

x² - 6x + 5 = 0 ← in standard form

(x - 1)(x - 5) = 0 ← in factored form

Equate each factor to zero and solve for x

x - 1 = 0 ⇒ x = 1

x - 5 = 0 ⇒ x = 5

Substitute these values into (2) for corresponding values of y

x = 1 : y = (2 × 1) + 3 = 2 + 3 = 5 ⇒ (1, 5)

x = 5 : y = (2 × 5) + 3 = 10 + 3 = 13 ⇒ (5, 13)

Solutions are (1, 5) and (5, 13)